2018
DOI: 10.1080/17549507.2018.1488990
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the telerehabilitation group aphasia intervention and networking programme on communication, participation, and quality of life in people with aphasia

Abstract: Results from this study suggest that the online delivery of a multi-purpose group intervention for people with aphasia can result in improved communication, communicative participation, and QOL. It also highlights the potential for intervention provided via telepractice to offer an alternative to face-to-face services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 37 publications
4
49
0
6
Order By: Relevance
“…The fact that we recruited 34 participants from 67 screens (50.7%) suggests that people with aphasia are willing to take part in studies of remote intervention. This was similarly the case in Pitt et al [36] where over 67% of those screened progressed to intervention. Our participants were, on average, younger than typical stroke survivors [68].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The fact that we recruited 34 participants from 67 screens (50.7%) suggests that people with aphasia are willing to take part in studies of remote intervention. This was similarly the case in Pitt et al [36] where over 67% of those screened progressed to intervention. Our participants were, on average, younger than typical stroke survivors [68].…”
Section: Discussionmentioning
confidence: 53%
“…There is growing evidence that telerehabilitation can be used to both assess [30,31] and treat [32][33][34] people with aphasia. While most applications of telerehabilitation have been delivered one to one, researchers in Australia have additionally explored the feasibility of delivering remote group therapy [35][36][37]. This team developed a 12 week (18 hour) programme of therapy called TeleGAIN, which aimed to improve communication related quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this model enabled people with PD to access an SLT-led group session, they were still required to travel to a central point to achieve this. A recent study in aphasia has demonstrated the feasibility of delivering online group therapy to people with aphasia living in their own homes (Pitt et al 2018). In this study, multi-point videoconferencing was used to connect to participants in their homes.…”
Section: Nature Of Technology-enabled Managementmentioning
confidence: 99%
“…Telerehabilitation has been developed a few decades ago aiming to overcome practical problems, such as a patient’s difficulty to reach the hospital, the lack of specialized centres in a patient’s place of residence, excessive costs of hospital management and incongruent timing of patients’ and health professionals’ activities. The need for intensive or prolonged treatments not feasible in hospital, the planning of home exercises and the need to address cognitive impairment in real life have also posed indication for telerehabilitation, providing prolonged benefits to patients with neurodegenerative diseases [ 6 ]. Recently, the use of telemedicine has become more and more important to public health due to coronavirus pandemic stimulating different telecommunication and digital technologies for cognitive, behavioural and psychological therapies.…”
mentioning
confidence: 99%